Penyuluhan Tentang Manfaat Literasi Kesehatan Terhadap Pencegahan Hipertensi - Watung, Grace; Sibua, Siska Sibua (Journal of Excellence Humanities and Religiosity, 2025)
The prevalence of hypertension in adults has almost doubled from 650 million in 1990 to 1.3 billion in 2019. Hypertension contributes to 10.8 million preventable deaths each year and 235 million years of life lost or living with disability. The purpose of this activity is to increase community knowledge about hypertension prevention through health literacy in Modayag Village community. The devotion method used is the pre-post test method through administering questionnaires about knowledge of hypertension prevention through health literacy. Respondents in this activity were 31 people from Modayag Village. The results of this service activity increased knowledge about health literacy towards the prevention of hypertension. This activity is very important because the community needs the availability of information about the prevention of hypertension through health literacy, so it is necessary to provide counseling or socialization about health literacy on the prevention of hypertension.